A Method to Determine the Torque Ripple Harmonic Reduction in Skewed Synchronous Reluctance Machines - César Gallardo; Carlos Madariaga; Juan A. Tapia; Michele Degano (Applied Sciences, 2023)
In this paper, a discrete skew methodology is presented to understand the effect of skewing angle on electromagnetic torque in SynRM design. A new approach is proposed to estimate the amplitude of each torque ripple component as a function of skewing angle. The reduction factor for each harmonic component is derived in general form, allowing for the determination of overall torque ripple waveform. The validity of the proposed method is evaluated through the examination of two SynRMs, resulting in a torque ripple reduction of up to 70%. The results obtained through the use of a proposed analytical ripple reduction estimator and FEA evaluation showed good agreement. The proposed skewing technique was applied on a previously optimized triple-barrier SynRM with a positive outcome: a consistent torque ripple reduction tackling relevant harmonic components. The analysis of harmonic distribution of torque ripple is mandatory for the selection of the optimal skewing strategy when following the proposed method, with two-step skewing recommended for mostly-purely-sinusoidal torque waveforms, and multi-step skewing recommended for machines with multiple higher-magnitude harmonic components.